The placental battlefield: viral strategies and immune countermeasures - Dhar, Ruby; Singh, Sunil; Sahoo, Om Saswat; Chandra, Nilesh; Gul, Anamta; Mukherjee, Indrani; Karmakar, Shreyashi; Amanullah, Mohammed; Karmakar, Subhradip (Frontiers in Immunology, 2025)
The placenta plays an essential role in connecting the maternal and fetal environments. It acts as both a protective barrier and a selective transport system during pregnancy. Despite its importance, we still do not fully understand how the placenta responds to viral infections, leaving a notable gap in maternal-fetal medicine. This review looks at how viral pathogens interact with placental tissue. It explores how viruses are transmitted, how the placenta’s immune system responds, and how infections affect pregnancy outcomes. We examined recent findings on how viruses can penetrate placental barriers, the molecular processes that lead to placental damage, and the long-term effects on fetal development. We gathered evidence from SARS-CoV-2, Zika virus, cytomegalovirus, and other viral infections to highlight common pathways and point out possible treatment targets. As new viral threats continue to challenge healthcare systems worldwide, understanding placental virology is crucial for safeguarding both maternal and fetal health. This review outlines potential future research paths and emphasizes the urgent need for placenta-specific antiviral strategies as new infectious diseases emerge.